Comparative study on satellite base air monitoring system / Norsyuhaimy Abdul Shukor - Abdul Shukor, Norsyuhaimy (2010)
The air quality indicator approximated by satellite measurements is known as atmospheric particulate loading, which is evaluated in terms of columnar optical thickness of aerosol scattering. The effect brought by particulate pollution has gained interest after recent evidence on health effects of small particles. This study uses an empirical model, based on actual air quality of particulate matters of size less than 10 micron (PMIO) measurements from to predict PMIO based on optical properties of satellite digital imagery. The digital image was separated into three bands assigned as red, green and blue for multispectral algorithm regression. The digital numbers were extracted corresponding to the ground-truth locations for each band and then converted to radiance and reflectance values. The digital numbers of the three bands were converted into irradiance and then reflectance. The atmospheric reflectance value was extracted from the satellite observation reflectance values subtracted by the amount given by the surface reflectance. The atmospheric reflectance values were later used for PMIO mapping using the calibrated algorithm. The PMIO map was color-coded and geometrically corrected for visual interpretation. This study indicates that PMIO mapping can be carried out using remote sensing technique.